Ameliorative effect and potential mechanism of hyperoside on diabetic retinopathy - Yu, Xu; Wu, Hao; Zhou, Lei; Wang, Gaoxiang; Sun, Xinyi; Miao, Junjun; Ben, Meijie; Shi, Rongwei; Wan, Shimei; Li, Shasha; Wang, Xiaoci; Zhou, Xiqiao; et al. (Frontiers in Endocrinology, 2025)
AimsThis study aimed to evaluate the role of hyperoside in ameliorating the retinal injury of diabetic retinopathy (DR) rats and the dysfunction of retinal endothelial cells (RECs) in high glucose.MethodsRECs were cultured in various groups including high glucose and different concentrations of hyperoside. The viability, migration, and tube formation of RECs and the expression of transforming growth factor-beta 1 (TGF-β1)/micro-RNA 200b (miR-200b)/vascular endothelial growth factor (VEGF) in each group were assayed. Sprague–Dawley rats were used for DR modeling and were treated with hyperoside. The tissue pathology of the rat retina and the expression of TGF-β1/miR-200b/VEGF in the retinal tissues of each group were examined.ResultsExcessive proliferation, migration, and tube formation of RECs were induced by high glucose. The retinal pathological changes and vasculopathy in DR rats were more serious compared with those in normal rats. The expression levels of TGF-β1 and VEGF in the high glucose-induced REC group and in DR rat retina were markedly upregulated, but those of miR-200b were noticeably downregulated. However, hyperoside could significantly inhibit the high glucose-induced overproliferation, migration, and tube formation of RECs, alleviate the retinal injury in DR rats, and reverse the expression of TGF-β1/miR-200b/VEGF in the high glucose-induced REC and DR rat retina, dose-dependently.ConclusionsHyperoside could ameliorate retinal injury in DR rats and the high glucose-induced dysfunction of RECs by regulating the TGF-β1/miR-200b/VEGF pathway.